UTILIZAÇÃO DA METODOLOGIA SEIS SIGMA PARA O DESENVOLVIMENTO DE SOLUÇÕES DE CONVERGÊNCIA FIXO E MÓVEL EM TELECOMUNICAÇÕES - Ribeiro, Jeferson Tavares (2005)
This work presents a case study, realized with a Services Leader Company of Electronic Cashiers based on ATMs (Automatic Teller Machines) located in public environments with 7 days a week and 24 hours a day operation. For this purposes, we use the Six Sigma Methodology to provide a low cost and high availability Telecom infrastructure. A new methodology based on operational cooperation built a service differentiation and SLA (Service Level Agreement) to improve quality of service with low costs using secure VPN technology based on Internet Protocol (IP). As a result, this work demonstrates that GPRS, ADSL and DIAL are best suited for TEF (Electronic Fund Transfer) data transmission providing a low cost and high quality solution.